Magnetic dehydrodipeptide-based self-assembled hydrogels for theragnostic applications - Carvalho, André (2019)
Self-assembled peptide hydrogels have emerged in recent years as the new paradigm in biomaterials research. We have contributed to this field the development of hydrogels based on dehydrodipeptides N-capped with naproxen. The dehydrodipeptide hydrogels can be loaded with drugs, thus being potential nanocarriers for drug delivery. In this work novel dehydrodipeptides containing tyrosine and aspartic acid amino acid residues N-capped with naproxen and C-terminal dehydrophenylalanine were prepared and characterized. Superparamagnetic iron oxide nanoparticles (SPIONs) were incorporated into the dehydrodipeptide-based hydrogels and their effect on the self-assembly, structure and rheological and magnetic properties of the hydrogels was studied. Magnetic hydrogels, with incorporated SPIONs, displayed concentration-dependent T2-MRI contrast enhancement. Moreover, upon magnetic excitation (alternating magnetic field –AMF–) the SPIONs were able to generate a significant amount of heat. Hence, magnetic hyperthermia can be used as a remote trigger for release of drug cargos and SPIONs incorporated into the self-assembled dehydrodipeptide hydrogels.